Leadership style and employees’ satisfaction in selected small and medium scale enterprises in delta state - Emmanuel Mitaire Tarurhor; Sunny Temile; Dadang Prasetyo Jatmiko; Biatna Dulbert Tampubolon (Journal of Management and Science, 2022)
Employees have resigned from well-paid organization due to the leadership style of their managers. This study examined the effect of leadership style on employees’ satisfaction in selected small and medium scale enterprises in Delta State, Nigeria. Sixty copies of questionnaires were distributed of which fifty-one were returned and used for this analysis. This survey instrument was adapted from both the Multifactor Leadership Questionnaire (MLQ) which measures transactional and transformational leadership style and the Minnesota Satisfaction Questionnaire (MSQ) which measures employee satisfaction. The study used STATA 13.0 statistical package. The results showed a positive and statistically significant relationship between employees’ satisfaction and leadership style when independent samples were treated separately (simple regression). However, when multiple regression models were applied, both results report positive relationship, but transactional leadership style now becomes statistically insignificant. It is recommended among other things that managing directors should select the right style of leadership that enhances their worker’s productivity and motivation.